Construção de literatura de cordel para educação em saúde alimentar de idosos comunitários - Tenório, Valeska Henrique Dias (2021)
INTRODUCTION: The aging process has been occurring in an accelerated and uneven way, which makes the development of articulated care actions and encouragement of the social inclusion of elderly people urgently to promote active aging. Adequate nutrition is a strong ally to reduce the vulnerability of the elderly and an essential item for the maintenance of health status. Thus, nutrition care has become increasingly routine and necessary. The importance of health education is vast and can help the elderly to change their lifestyle habits, considering that eating behaviors have a great impact on the health/disease situation. OBJECTIVE: Analyze scientific production that addresses the meaning of healthy eating for the elderly; understand the social representations of food for elderly community members; build, based on the findings, a health education instrument with guidelines aimed at adopting a healthy diet based on accessible foods for the geron. METHOD: This is a methodological study structured in three stages: conducting an integrative literature review; empirical investigation with elderly people from a community accompanied by a team from the Family Health Unit and, finally, construction of an instrument in the Cordel Literature format about the possibilities of adopting healthier eating practices by elderly people. The integrative review consisted of 22 carefully selected articles. The sample of the empirical study was composed of 150 elderly community members of both sexes. After collection, the data were processed in the SPSS and IRAMUTEQ software, in addition to organizing the Collective Subject Discourse for content analysis and preparation of the last phase of the research, the educational Cordel. RESULTS AND DISCUSSION: In the results of the integrative review, references to the social context in which the elderly are inserted and their relationship with food were observed; the eating patterns established as a daily practice and the food barriers faced by the elderly, with health service professionals having a fundamental role in overcoming such obstacles. The elderly people interviewed represented food as being based on three core meanings: Eating habits of elderly people; Food as a basis for family reunion; and Healthy eating as a necessary health care. In this sense, the construction of a health education instrument, in the form of a string, intends to bring the elderly closer to the theme “Food” in a simple and playful way. FINAL CONSIDERATIONS: It is expected that the development of food and nutrition education actions for the elderly will help in the adequate supply of nutrients, encourage social interaction and, thus, improve their quality of life. It emphasizes the importance of the nutritionist in primary care to allow favorable adaptations to the physiological needs of the elderly, understanding the social context and their life history. Based on these findings, the instrument constructed in a string format deals with guidelines for the adoption of a healthy diet, in a playful way, taking into account the pleasure of eating and foods accessible to the elderly.